A Comparative Study of the Formation of Contracts in Japanese, English, and German Law - Suzuki-Klasen, Anna Katharina (Recht in Ostasien, 2022)
The basic elements of a contract, namely, offer and acceptance, the intention to be bound, and consideration, and requirements of form found in English, German, and Japanese law are compared against the background of their historical development, the legal consciousness and practices existing in these countries. In this way, awareness is built both of the theoretical or practical differences and the underlying socio-cultural reasons. This in turn aids in the comprehension of why certain variations exist, which, although sometimes deceptively small, may have great importance for contracting in practice.